Evaluation of Cysteinyl Leukotriene Signaling as a Therapeutic Target for Colorectal Cancer - Burke, Lorraine; Butler, Clare T.; Murphy, Adrian; Moran, Bruce; Gallagher, William M.; O'Sullivan, Jacintha; Kennedy, Breandán N. (Frontiers in Cell and Developmental Biology, 2016)
Colorectal cancer is the third most common cancer worldwide and is associated with significant morbidity and mortality. Current pharmacotherapy options include cytotoxic chemotherapy, anti-VEGF and anti-EGFR targeting drugs, but these are limited by toxic side effects, limited responses and ultimately resistance. Cysteinyl leukotriene (CysLT) signaling regulates intestinal homeostasis with mounting evidence suggesting that CysLT signaling also plays a role in the pathogenesis of colorectal cancer. Therefore CysLT signaling represents a novel target for this malignancy. This review evaluates reported links between CysLT signaling and established hallmarks of cancer in addition to its pharmacological potential as a new therapeutic target.